1990
DOI: 10.1177/073428299000800202
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hispanic and Anglo Graduate Record Examination Scores and Academic Performance

Abstract: The Graduate Record Examination (GRE) Verbal, Quantitative, and Analytic scores and undergraduate and graduate grade-point averages (U-GPA and G-GPA) for 320 Hispanics and 632 Anglos admitted to graduate school at the University of Texas at El Paso over the past 5 years were evaluated. Multivariate analyses revealed that Anglos scored significantly higher than Hispanics on both U-GPA and G-GPA and all three GRE scores. Multiple regression analyses for the ethnic group, with U-GPA and GRE scores used to predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 6 publications
2
10
1
Order By: Relevance
“…This indicates that Doctoral students who had higher CGPAs were more likely to have higher UGPAs (β = .13). This finding is consistent with that found by Whitworth and Barrientos (1990).…”
Section: Relationship Between the Composite Predictor And Cgpasupporting
confidence: 94%
See 4 more Smart Citations
“…This indicates that Doctoral students who had higher CGPAs were more likely to have higher UGPAs (β = .13). This finding is consistent with that found by Whitworth and Barrientos (1990).…”
Section: Relationship Between the Composite Predictor And Cgpasupporting
confidence: 94%
“…While small correlations typical in GRE validation studies were expected due to a ceiling effect, e.g., restriction of range of scores (Ingram, 1983;Kuncel et al, 2001;Mehrens & Lehmann, 1987;Schmidt & Hunter, 1981;Schneider & Briel, 1990), criterion unreliability( (Kuncel et al, 2001;Mehrens & Lehmann, 1987;Schmidt & Hunter, 1981), and compensatory selection (Ingram, 1983;Schneider & Briel, 1990;Whitworth & Barrientos, 1990), the present study found smaller correlations than those in the previous studies. …”
Section: Relationship Between Gre Scores and Fgpacontrasting
confidence: 69%
See 3 more Smart Citations